The traditions of our people to teach young people how to heal through magic and magical phenomena - Kurbanbaeva Asel Jumabaevna (Genius Journals, 2021)
In ancient times, our people lived close to nature, gained experience by observing the events that occur with the change of weather and the change of seasons. They drew their own conclusions from their experiences. Man learned the necessary lessons from various natural phenomena and tried to understand them. The sudden illness or sudden death of a healthy person who was standing up made people marry, think, and determine its meaning. That is why the people were looking for the reasons and secrets. To do this, he tried to understand the mysterious phenomena of the environment, nature. He knew in advance the dangers. On the plus side, Karakalpak folk healers found some types of diseases to be right and sought treatment, while others were able to cure them. Over time, the concepts, the accumulated knowledge expanded and the traditions of treatment also developed. The people of Karakalpakstan, based on their way of life, have paid attention to the events of the changing seasons, which are shrouded in natural phenomena. Although the public opinion is not very high, experience has shown that various natural phenomena can be harmful to human health through observations.
Keywords: Healer; magic; talisman; tradition